Using CaCO3-doped package to improve correlated color temperature uniformity of white light-emitting diodes - My Hanh Nguyen Thi; Nguyen Thi Phuong Loan; Thuc Minh Bui; Hoang Van Ngoc (Institute of Advanced Engineering and Science, 2021)
The white light-emitting diode (WLED) has been the most advance lighting method currently, however, the fabrication process of this configuration still has drawbacks which negatively affect its color quality. This research was conducted to provide a method for WLED’s lighting output enhancement. Since CaCO3 particles are excellent for thermal stability enhancement, especially when being combined with an adhesive substance, we decided to integrate CO3 particles into resin matrix such as melamine formaldehyde (MF) and investigate their influences on the optical properties, including color uniformity and lumen output, of the WLED. The results showed that CaCO3 and MF resin are beneficial to the light scattering efficiency, which results in higher luminous flux and chromatic quality for WLED packages. In addition to that, the appropriate amounts of MF resin and CaCO3 for reaching the best lumen efficiency and color quality are figured out at 1% and 10%, respectively. Moreover, another advantage of using MF resin and CaCO3 for fabricating WLEDs is cost effectiveness. Hence, it has turned out that CaCO3 and MF resins can be potential materials for next high-quality WLED generations.